2017
DOI: 10.1101/143354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classes and continua of hippocampal CA1 inhibitory neurons revealed by single-cell transcriptomics

Abstract: Understanding any brain circuit will require a categorization of its constituent neurons. In hippocampal area CA1, at least 23 classes of GABAergic neuron have been proposed to date. However, this list may be incomplete; additionally, it is unclear whether discrete classes are sufficient to describe the diversity of cortical inhibitory neurons, or whether continuous modes of variability are also required. We studied the transcriptomes of 3663 CA1 inhibitory cells, revealing 10 major GABAergic groups that divid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(165 citation statements)
references
References 83 publications
(124 reference statements)
16
148
1
Order By: Relevance
“…In line with this, a significant portion of ebGABAs project to the medial septum 12 . In the present study, we have found that ebGABAs express combinations of molecular markers typical of two extra classes of GABAergic projection cells: strong nNOS-expressing backprojection cells, likely innervating dentate gyrus and CA3 14,18 , and M2R-expressing retrohippocampal cells innervating subiculum and retrosplenial cortex 19 . Combined with the fact that biocytin-filled ebGABAs exhibited little local axonal arborization, these data indicate that ebGABAs could form several classes of projection cells innervating various target regions.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In line with this, a significant portion of ebGABAs project to the medial septum 12 . In the present study, we have found that ebGABAs express combinations of molecular markers typical of two extra classes of GABAergic projection cells: strong nNOS-expressing backprojection cells, likely innervating dentate gyrus and CA3 14,18 , and M2R-expressing retrohippocampal cells innervating subiculum and retrosplenial cortex 19 . Combined with the fact that biocytin-filled ebGABAs exhibited little local axonal arborization, these data indicate that ebGABAs could form several classes of projection cells innervating various target regions.…”
Section: Discussionsupporting
confidence: 55%
“…To estimate the cell types comprised in the ebGABA population, we examined the combinatorial expression of molecular markers in these cells. In the hippocampus, strong nNOS+ cells are GABAergic projection cells that also express SOM, NPY and M2R 14 and are likely to innervate the dentate gyrus and CA3 18 . We confirmed that strong nNOS+ ebGABAs belong to this cell type by finding that these cells often co-expressed SOM (94 ± 11%, n=4 brains), NPY (93 ± 13%, n=5 brains) and M2R (62 ± 27%, n=3 brains, Figure 2c and Supplementary Figure 3).…”
Section: Adult Ebgabas Exhibit Features Of Long-range Projecting Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…While neurons and glial cells traditionally have been classified into sub-categories based on morphological and anatomical criteria or differences in neurotransmitter repertoire, a new and more fine-grained view of neurons and glial cell sub-types is now emerging as a result of recent transcriptomic analyses of the brain at the single-cell level. Thus, more than 500 molecularly distinct classes of neurons and glial cells have been identified in the mouse brain [1,2], and information about the cellular composition of specific brain regions is increasing rapidly [2][3][4][5][6][7][8]. Insights into the developmental trajectories for the different cell lineages-proceeding from immature progenitors to specialized cells -are generated by computational analyses of single-cell transcriptomes derived from different developmental stages [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the hippocampus plays a key role in memory consolidation allowing the long-term storage of recently acquired events. Hippocampal circuits are regulated by a large variety of local inhibitory interneurons, whose identities and functions are under intense scrutiny (Harris et al, 2018, Pelkey et al, 2017, Parra et al, 1998. These interneurons are controlled by complex neuromodulatory systems ensuring their coordinated functions to shape behavioral responses (Klausberger and Somogyi, 2008).…”
Section: Introductionmentioning
confidence: 99%